2013 Seventh International Conference on Complex, Intelligent, and Software Intensive Systems 2013
DOI: 10.1109/cisis.2013.17
|View full text |Cite
|
Sign up to set email alerts
|

Digital Collaboration Network for SMEs: Awareness of ICT and Perceived Outcome

Abstract: This study aims to analyze degree of awareness of ICT and perceived outcome of SMEs to be involved in digital collaboration networks. Digital Collaborative Networks can be assumed as a digital highway to accelerate economic growth in certain industrial sector. In this network, stakeholders can be formed in a unity to be voluntary sharing their business resources. Moreover, this community network is based on the spirit of cooperation and collaboration to build the economic strength of the nation. This study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Another major concern in realizing e-collaboration is the lack of IT capability in rural areas [42,45], including IT infrastructure and digital literacy. The lack of IT capability addresses IT standards, models, or governance in an ecollaboration that does not yet exist [36,57].…”
Section: -1-e-collaboration Success Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another major concern in realizing e-collaboration is the lack of IT capability in rural areas [42,45], including IT infrastructure and digital literacy. The lack of IT capability addresses IT standards, models, or governance in an ecollaboration that does not yet exist [36,57].…”
Section: -1-e-collaboration Success Factorsmentioning
confidence: 99%
“…Thus, e-collaboration is not only a platform but also a business with a new management method [46,48]. Markets can change quickly, and the level of competition is high enough to encourage a business to find new ways to maintain its business [45,51,56]. E-collaboration also provides entrepreneurs opportunities to build their digital business content, products, and services and continuously innovate [16,36].…”
Section: -1-e-collaboration Success Factorsmentioning
confidence: 99%
“…It is essential to support SMEs' growth and help small businesses gain a competitive advantage through special programs, funding, policies, and counseling on account of their planned behavior [101,125] and strengthen their support for digital transformation goals through technology acceptance [102,103,126]. Fachrunnisa et al (2013) [98] found that SMEs perceive more incredible benefits or outcomes when collaborating virtually. The government and other stakeholders must support this community network in several ways.…”
Section: Discussionmentioning
confidence: 99%
“…A thorough literature review found that most studies have been conducted in Western countries. Despite this, a few studies and reports focus on the Saudi SMEs' towards digitization [5,7,15,34,36,49,52,73,[75][76][77]94,98,99]. The study focuses on the Ha'il province, located in the northern region of Saudi Arabia, having 103,887 km 2 estimated area, and 746,406 population [100].…”
Section: Rationale Of the Studymentioning
confidence: 99%